PENDEKATAN KETERAMPILAN PROSES DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA - Thalib, Abd. (Pedagogik Journal of Islamic Elementary School, 2018)
This research is a classroom action research. This research was carried out at Ma’arif MakassarVocational School. This study involved class X students with a total of 30 students. the purposeof this study was to improve the learning outcomes of Indonesian language for students of classX Ma’arif Makassar Vocational High School. This study uses 2 cycles with each one cycle of 3meetings. Based on the implementation of learning and discussion of the influence of theprocess skills approach in class X. So the authors can conclude that efforts to improve learningoutcomes and student involvement in the learning process in Indonesian subjects can be donewith active learning. The results of this study prove that the process skills approach is able toincrease student activity and involvement in the learning process and also improve studentlearning outcomes.